2010
DOI: 10.2202/1469-3569.1310
|View full text |Cite
|
Sign up to set email alerts
|

On the Use of FTAs by Japanese Firms: Further Evidence

Abstract: The paper examines the use of free trade agreements (FTAs) by Japanese firms. The FTAs analyzed include Japan's FTAs with Mexico, Malaysia and Chile. Based on 1,688 responses to a questionnaire survey conducted in 2008, the study finds that the utilization rate of FTAs ranges between 32.9% (Japan-Mexico FTA) and 12.2% (Japan-Malaysia FTA). The survey results and the statistical analysis of the determinants of the use of FTAs reveal obstacles to using FTAs that include difficulty in obtaining the certificate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
42
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 1 publication
4
42
0
Order By: Relevance
“…Using a sample of Japanese firms, Takahashi and Urata (2008) examined the influence of several enterprise characteristics (e.g. firm size, trading relations with FTA partners, the ratio of overseas sales to total sales, overseas business bases, and manufacturing membership) on FTA use.…”
Section: Free Trade Agreement Preference Utilizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a sample of Japanese firms, Takahashi and Urata (2008) examined the influence of several enterprise characteristics (e.g. firm size, trading relations with FTA partners, the ratio of overseas sales to total sales, overseas business bases, and manufacturing membership) on FTA use.…”
Section: Free Trade Agreement Preference Utilizationmentioning
confidence: 99%
“…Furthermore, there may be methodological gaps in these studies. For instance, in Takahashi and Urata (2008) the exclusive use of dummy variables as regressors resulted in a model with weak explanatory power. On the other hand, Hiratsuka et al (2009) employed a sophisticated panel data analysis of a large sample of Japanese MNCs but only a few explanatory variables were explored, which could contribute to omitted-variable bias in the results.…”
Section: Free Trade Agreement Preference Utilizationmentioning
confidence: 99%
“…Using a sample of Japanese firms, Takahashi and Urata (2008) examined the influence of several enterprise characteristics (e.g. firm size, trading relations with RTA partners, the ratio of overseas sales to total sales, overseas business bases, and manufacturing membership) on RTA use.…”
Section: The Regional Trade Agreement Debate In Relation To Southeastmentioning
confidence: 99%
“…Takahashi and Urata (2008) concluded that large firms were more likely to use RTAs, reflecting the costs of such practices, and that trading experience in RTA markets also influenced the likelihood of RTA use.…”
Section: The Regional Trade Agreement Debate In Relation To Southeastmentioning
confidence: 99%
“…Previous studies at the country and industry levels, however, suggest that FTA preference utilization rates-based on shares of export value enjoying preferences-are low in East Asian countries and that FTAs are underutilized (Baldwin 2006;World Bank 2007). A firmlevel study of Japan's FTAs also reported modest preference utilization rates and related this to the low volume of trade with FTA partner countries (Takahashi and Urata 2008). Accordingly, Asian FTAs are often viewed as discriminatory and a drain on scarce trade negotiation capacity in developing countries (Bhagwati 2008).…”
Section: Challenge 1: Improving Firm-level Use Of Fta Preferencesmentioning
confidence: 99%